Pregnancy, motherhood and elite sport: A review of athletes' experiences - Sebastia-Amat, S.; Ortega-Corcoles, M.; Montava-Gisbert, M.; Garcia-Jaén, M.; El Klahi, J.; Sanchis-Soler, G. (Journal of Physical Education and Sport, 2024)
Elite sports and motherhood present unique challenges for women athletes. Despite the increasing participation of women in sports, there is a significant lack of research on the experiences of elite athletes during pregnancy and the postpartum period. This gap leads to confusion and anxiety about how to manage training and performance while considering motherhood. For elite women athletes, the decision to become a mother or plan a pregnancy can be especially difficult. Developing strategies and support systems that allow athletes to make this decision without negatively affecting their sports careers would be highly beneficial. However, it is first necessary to identify and understand the obstacles or barriers that affect both the decision to have a child and the course of the pregnancy itself. The objective of this review is to analyse qualitative studies that examine the experiences, challenges, and perspectives of elite women athletes regarding pregnancy. The review followed the Metaethnographic method developed by Noblit and Hare (1988), which involves a systematic analysis of qualitative research. The final search included only articles published in English and Spanish within the last ten years. The selected studies revealed that the main concerns for athletes include the fear of losing contracts and funding, uncertainty about training protocols, and lack of institutional support. Many athletes also reported feeling abandoned during pregnancy, exacerbating their stress. While some sports federations have begun implementing maternity leave policies, these are not universally applied, leading to disparities across different sports. The findings highlight the need for more comprehensive support systems for athletes who wish to become mothers. The importance of role models and research to guide athletes in decision-making processes is also emphasized. Legislative measures are essential to address discrimination and ensure that athletes can pursue motherhood without jeopardizing their careers. Finally, this review concludes that further research is needed to develop evidence-based guidelines and policies that support athletes in balancing their dual roles as mothers and elite competitors.